Bone availability for alveolar grafts at different donor sites: a narrative review (Research, Society and Development, 2024)
Alveolar bone grafting is a well-established procedure, but it is still a challenge, especially in patients with cleft lip and palate. The iliac bone is often used as a donor site for an autogenous bone graft, but it can also be the tibia, calvaria or even the chin. The aim of this article is to present a literature review on the availability of bone for grafts in different donor sites. This review examined 26 studies obtained from online search platforms from 2000 to 2024. The studies investigated bone availability for alveolar grafts at different donor sites. In addressing these issues, we searched the literature for alternatives for alveolar bone grafting, whether common or secondary in residual cleft palate patients with cleft lip and palate, so that, with this knowledge, patients have greater well-being and safe options when undergoing this surgical procedure. The different donor sites discussed in this review have shown excellent results, with good availability of bone for use in bone grafts in cases where there are jaw defects. The decision as to which donor site is used depends on the type of defect. Comparing the bone of the skullcap with intraoral donor sites, the availability of bone in the skullcap can be up to 3 times greater than in other regions, such as the mandible, and approximately 2 times greater when compared to the mandibular symphysis.